Efektivitas Hedging Kontrak Futures Komoditi Emas Dengan OLEIN - Fitri Ismiyanti; Hendra Ima Sasmita (Jurnal Manajemen Teori dan Terapan | Journal of Theory and Applied Management, 2011)
This research is for comparing hedging effectiveness in gold and olein commodity. Using Ordinary Least Square (OLS) model to determine the hedge ratio, it’s found that olein hedge ratio is bigger than gold hedge ratio. The value of olein hedge ratio is bigger than gold hedge ratio indicate that to eliminate loss in olein spot market is needed a lot of futures contract as compared to eliminate loss in gold spot market. However, independent t-test to return hedged variance both commodity show there is no different variance. This mean the return hedged variance of gold commodity has the same value with olein return hedged variance. So, handling the systematic risk of olein hedger have the same as of gold hedger handling. With the result that, if doing hedging strategy and there is no same instrument to be hedged in futures market, so hedger may considering to use cross hedging strategy, but previously determined first the optimum hedge ratio, because the optimum hedge ratio can reduce the variance return caused by market risk (systematic risk).